Experience of the Club Foot Management by Ponseti Technique (Journal of Pakistan Orthopaedic Association, 2014)
Objectives: To find out the results of Ponseti for the treatment of clubfoot.Design: Prospective and Experimental.Material and Methods: Sixty patients comprising both gender (Male & Female) were included in this study, age less than 09 months with Congenital Telipes Equinovarus were evaluated by Pirani Scoring method, treated by Ponseti Technique having two years follow up.Results: - Out of 60 Patients, males 32(53.4%) and females were 28(46.7%). In this study 24(40%) Bilateral and 36(60%) were Unilateral. According to Pirani Scoring Method; 40(66.6%) patients severely deformed and 20(33.4%) were moderately deformed, percutaneous tenotomies of tendo achillis was done in 30(50%). Three patients developed complications, two developed recurrence and operated by Posteromedial release and one developed Plaster Sore.Keywords: - Talipes Equinovarus, Ponseti Procedure, Serial casting.